So Close to the State/s : The Emergence of Canadian Feature Film Policy - Dorland, Michael (Book collections on Project MUSE., 1998)
"This book examines in detail the formation of Canadian feature film policy from the 1950s to the present. It pays special attention to the role played by producers, filmmakers, and government agencies in relation to the changing production practices brought about by Canadian television."--Jacket.